Nonlinear Approaches in Engineering Applications Energy, Vibrations, and Modern Applications (Springer International Publishing, 2018)
This book analyzes the updated principles and applications of nonlinear approaches to solve engineering and physics problems. The knowledge on nonlinearity and the comprehension of nonlinear approaches are inevitable to future engineers and scientists, making this an ideal book for engineers, engineering students, and researchers in engineering, physics, and mathematics. Chapters are of specific interest to readers who seek expertise in optimization, nonlinear analysis, mathematical modeling of complex forms, and non-classical engineering problems. The book covers methodologies and applications from diverse areas such as vehicle dynamics, surgery simulation, path planning, mobile robots, contact and scratch analysis at the micro and nano scale, sub-structuring techniques, ballistic projectiles, and many more. Explores the nonlinear approaches that open avenues to better, safer, cheaper, and more cost-effective consumption of power and raw materials; Exposes readers to a broad range of practical topics and approaches; Contains a strong emphasis on application, physical meaning, and the methodologies of the approaches discussed.